A highly potential cleavable linker for tumor targeting antibody-chemokines. Issue 6 (13th April 2022) - Mohammadi, Mozafar; Rezaie, Ehsan; Sakhteman, Amirhossein; Zarei, Neda
Abstract: Chemokines are the large family of chemotactic cytokines that play an important role in leukocyte movement and migration stimulation. Until now, several antibody-cytokine (chemokine) fusion proteins have been investigated in clinical trials because of their ability to evoke the circulating leukocytes far from the tumor site. In this case, creating the concentration gradient regarding the chemokine is very important to recruit the circulating leukocytes with maximum performance to the tumor environment. To achieve a proper gradient, the chemokine separation from the tumor antigen-bounded antibody can be very crucial. Thus, we designed a novel linker that can be cleaved by enzymes presented around the tumor site including cathepsin B, urokinase-type plasminogen activator (uPA) and matrix metalloproteinases (MMPs). Also, it can inhibit tumor progression by competing with the native substrate of key proteases in the tumor microenvironment. The proposed linker was evaluated using some bioinformatics approaches. In silico results showed that the linker is structurally stable and could be detected and cleaved using the mentioned enzymes. Communicated by Ramaswamy H. Sarma